Free ultra-groups, generators and relations - Tolue, B.; Zolfaghari, P.; Moghaddasi, Gh. (Algebra and Discrete Mathematics, 2019)
In this paper, we intend to define an ultra-group by its presentation. The attitude of the presentation for a group was the key for us to investigate in this area. Instead of writing whole elements of an ultra-group, we denote it by its generators and the relations among those generators. A general computational approach for finitely presented ultra-groups by quotient ultra-groups and subultra-groups is described and some examples are presented. It is the way that can clarify the structure of an ultra-group quicker than having just a list of elements.